2023
DOI: 10.1101/2023.01.18.524544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA sequencing identifies lung cancer lineage and facilitates drug repositioning

Abstract: Breakthrough therapies recently improve survival in lung adenocarcinoma (LUAD), yet we still lack a paradigm to support prospective confirmation. To classify three clusters including bronchioid, neuroendocrine, and squamoid, the non-negative matrix factorization (NMF) algorithm was first performed at The Cancer Genome Atlas (TCGA), Clinical Proteomic Tumor Analysis Consortium (CPTAC), Gene Expression Omnibus (GEO) and preclinical models. In terms of prognostic value, the squamoid cluster is of poor prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Immune checkpoint levels are higher in LUSC than in LUAD, which exhibits activated MHC-II ( 56 ). Our previous findings also indicated that different TME profiles are associated with distinct subtypes, such as the squamous subtype having an increased CXCL13 , EPSTI1 , and CDK1 positive subpopulation compared to the bronchioid subtype ( 9 ). Apart from this, populations previously negative for NKX2-1 and with solid pathology exhibited higher proportions of PD-L1.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Immune checkpoint levels are higher in LUSC than in LUAD, which exhibits activated MHC-II ( 56 ). Our previous findings also indicated that different TME profiles are associated with distinct subtypes, such as the squamous subtype having an increased CXCL13 , EPSTI1 , and CDK1 positive subpopulation compared to the bronchioid subtype ( 9 ). Apart from this, populations previously negative for NKX2-1 and with solid pathology exhibited higher proportions of PD-L1.…”
Section: Discussionmentioning
confidence: 66%
“…We used the random effects model to validate that high scores were a factor in unfavorable prognosis, after detecting no significant heterogeneity across the datasets (HR =1.21; 95% CI: 1.05–1.4; Figure 4F ). Immune-related S3 and squamous clusters with a poorer prognosis were found to have a higher score ( Figure 4G ) ( 9 , 35 ). Combined with our results, a subset of the population with a poorer prognosis may be suitable for ICIs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations